Altered Thyroid Function Tests Observed in Hypophosphatasia Patients Treated with Asfotase Alfa. (28th October 2021) - Kato, Hajime; Hidaka, Naoko; Koga, Minae; Kinoshita, Yuka; Nangaku, Masaomi; Makita, Noriko; Ito, Nobuaki
Abstract : Background . Asfotase alfa is the only approved treatment that can normalize mineralization in patients with hypophosphatasia (HPP). Its interference in alkaline phosphatase (ALP) dependent immunoassays has been reported. Objective . To describe thyroid function tests interfered with by asfotase alfa and elucidate the underlying mechanism. Patients and Methods . Three patients with HPP treated with asfotase alfa were included. Thyroid hormone levels measured using five different immunoassays with or without ALP as a labeling enzyme during asfotase alfa treatment were evaluated. Results . After the initiation of asfotase alfa, three HPP patients showed low free triiodothyronine (FT3) and free thyroxine (FT4) measured with AIA-2000 (Tosoh, Tokyo, Japan), an enzyme immunoassay system that uses ALP as a labeling enzyme, but their thyroid-stimulating hormone (TSH) levels were within the normal range. The other CLEIA system using ALP as a label, AIA-CL2400 (Tosoh, Tokyo, Japan), and ALP-independent immunoassay systems demonstrated normal FT3 and FT4 levels. These data suggested that although the thyroid function of these three patients was normal, asfotase alfa interfered with the thyroid hormone measurements made with AIA-2000. AIA-2000 and AIA-CL2400 adopted one-step and delayed one-step measurements, respectively, and the same antibody was used for both immunoassays. However, asfotase alfa may be absorbed on the magnetic beads used in the AIA reagent with the AIA-2000 system but not absorbed on the microparticles used in AIA-CL2400. Conclusion . Clinicians should be aware of the possible interference in thyroid function measurements by adopting specific types of immunoassays in asfotase alfa-treated HPP patients.